Modeling and Validation of the Dynamic Host Configuration Protocol with Colored Petri Nets - Farhad Soleimanian Gharehchopogh; Reza Soufizadeh (Institute of Advanced Engineering and Science, 2012)
Petri Networks with a graphical language are based on mathematical logic which have many uses and have capability for modeling and validation of distributed systems and concurrent applications. Colored Petri Networks (CPNs) are a type of Petri Network models that are used in modeling of systems which contain discrete and scattered events. In general, CPNs are used to evaluate system performance and demonstrate the correctness of systems. Dynamic Host Configuration Protocol (DHCP) is one of the main systems of protocols special for servers that are used for dynamic allocation of IP to the network computers (clients). In this paper, we highlight to analyze the correctness and authenticity of DHCPs with the use of CPNs with using the CPN Tools and to prove the accuracy of our protocol's performance.DOI:http://dx.doi.org/10.11591/ijece.v2i3.488